Digital Pengenalan Digital Dalam Membentuk Milenial Kreatif Untuk Menghadapi Era Society 5.0 Di Kabupaten Enrekang - Hutami Endang; Andi Jamiati Paramita; Ahmad Dzulfajri Syahruddin; Muhammad Syafaat; Ismaya Ismaya (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Enrekang Regency, South Sulawesi province is one of the regencies in Indonesia that must prioritize the millennial generation who are creative with digital in the era of society 5.0. The introduction and training activities for the proto.io platform and google site data collection methods are described as follows: a) The preparation stage, is a planning team coordination activity that collects data on community service needs and consolidation with the Muhammadiyah University of Enrekang related to issues and potentials , b) The implementation stage, including training on the proto.io platform and the google site. During the activity, the lecture and practice methods were accompanied by demonstrations where participants were provided with modules for practicum. The background of this collaboration is the need to provide a basis for digitization and understand the relevance of technology in the era of society 5.0. With this activity, the organizers realize how important technology is in this day and age. Participants also realized that currently there are many facilities on the internet that can be used to support participants' creativity.